Aninvestigation the Influence of Emotional Intelligence on Social Capital Using Hierarchical Model (Case Study: Shahid Chamran University Staff) - abbasali rastegar; rasoul gholamzadeh; hossein farsizadeh (توسعه اجتماعی, 2015)
This study seeks to develop and evaluate the hierarchical model of emotional intelligence and its impact on social capital. The central idea of these two concepts can be summarized in a sentence: relations are important. Method of this study in terms of purpose is application and base on data collection is descriptive – survey. The populations are shahid Chamran University of Ahvaz employees. The sample consisted of 122 employees that use random samplings to test the hypotheses are selected. Data was collected using standard questionnaire and analyzed with structural equation modeling and partial least squares approach. The results indicate direct impact of emotional intelligence on social capital.